Weighted Relational Models of Typed Lambda-Calculi - Laird, Jim; Manzonetto, Giulio; McCusker, Guy; Pagani, Michele (2013 28th Annual ACM/IEEE Symposium on Logic in Computer Science, 2013)
The category Rel of sets and relations yields one of the simplest denotational semantics of Linear Logic (LL). It is known that Rel is the biproduct completion of the Boolean ring. We consider the generalization of this construction to an arbitrary continuous semiring R, producing a cpo-enriched category which is a semantics of LL, and its (co)Kleisli category is an adequate model of an extension of PCF, parametrized by R. Specific instances of R allow us to compare programs not only with respect to "what they can do", but also "in how many steps" or "in how many different ways" (for non-deterministic PCF) or even "with what probability" (for probabilistic PCF).